Perhitungan Burn Up Model Assembly Heksagonal pada Reaktor SCWR Menggunakan Bahan Bakarr Thorium - Mey Puji Astuti; Yanti Yulianti; Posman Manurung; Simon Sembiring (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
The research about the calculation of burn-up model of the hexagonal assembly in SCWR reactor using thorium as fuel materials has been done. This research uses thorium-232 and uranium-233 as fuel materials. Calculations were performed using the ASMBURN code in the SRAC program, by determining fuel enrichment, cell radius, analyzing atomic density after burn up, increasing burn up level, and change of linear heat. The calculation results obtained show the value of efficient fuel enrichment at 4% enrichment, with 0.3902 cm of fuel cell radius, 0.4508 cm of cladding, and 0.5586 cm of moderator. The atomic density of Th232 decreased for each burn-up period meanwhile, the atomic density of U233, U235, and Pu239 increased. The keff value will decrease along with the addition of burn-up and greater change of linear heat.